Niveles de glucosa plasmaticos en personas adultas de ambos sexos del area administrativa de la Universidad Nacional de Trujillo en el mes de diciembre del 2009 - Miñano Muñoz, Leonid Ismael (2010)
During the last decade, the importance of glycemic control in preventing various diseases, mainly diabetes mellitus, has been clearly demonstrated. Evaluated the glucose levels in 80 adult volunteers of both sexes in the administration area of the National University of Trujillo in the month of December 2009, divided into 3 groups between the ages: 28-42,43-57,58 -72 years, taked the fasting blood sample, before collecting their data using a survey, processed the blood samples enzymatic method (Glucose Oxidase - Peroxidase), evaluating the results and then ordered according to parameters set, found that 57.50% had normal blood glucose levels, decreased levels 2.5% and 40% increased levels of glucose. Concluding that the major percentage of the population had normal glucose levels, later gave the necessary information to each person with the deliveryofhimresult